Graphene-based dual functional metadevice in the THz gap - Ghosh S.K.; Das S.; Bhattacharyya S. (My University, 2025)
This paper presents a graphene-metal dual functional metadevice to provide two separate applications simultaneously, viz., absorption and cross-polarization conversion (CPC) of the electromagnetic (EM) wave without any structural deformations in the terahertz (THz) gap under two different biasing conditions. The meta-atom of the device bears stacked layers of metallic elliptical-shaped split rings, a thin zinc oxide (ZnO) layer, a slotted graphene layer printed over another ZnO layer backed by a continuous gold plate. It provides more than 70% absorptivity over a bandwidth of 3.40 THz (4.25 THz and 7.65 THz), with 90% absorptivity peak at 6.84 THz when the externally applied static electric field (ξ) on the patterned graphene surface is 8.52 V/nm. The change of the ξ to a value of 0.44 V/nm enables the device to produce a CPC ratio (CPCR) above 90% over a bandwidth of almost 3.87 THz (2.22 THz and 6.09 THz), with near unity polarization conversion ratio peaks occurring at 2.38 THz, 3.80 THz, and 5.82 THz. Both findings have been validated using an exhaustive equivalent circuit analysis. The design possesses ultrathin properties (λ0/12.49), along with compactness (λ0/5), which has been improved significantly compared to their microwave counterparts. The proposed metadevice finds useful applications in THz sensing, stealth technology, THz communication, detection, polarization manipulation of EM waves, etc. © 2021 Optica Publishing Group